An Improved Scalable Process for the Synthesis of (S,S)-DACH-Ph Trost Ligand - Zhang, Yongda; Chong, Eugene; White, Jada A. H.; Radomkit, Suttipol; Xu, Yibo; Kosnik, Stephanie C.; Lorenz, Jon C. (Synlett, 2022)
An improved chemical process has been developed for the synthesis of (S,S)-DACH-Ph Trost ligand. The amidation of 2-diphenylphosphinylbenzoic acid and (S,S)-diaminocyclohexane is promoted by stoichiometric CDI and catalytic imidazole hydrochloride. The resulting product, (S,S)-DACH-Ph Trost ligand, is isolated as a white solid in 80% yield with >99% ee by simple filtration without column chromatography. The current facile process is also demonstrated on kilogram scale.
Keywords: Trost ligand; DACH-Ph; coupling; 2-diphenylphosphinylbenzoic acid; chiral diaminocyclohexane; CDI; imidazole hydrochloride; kilogram